“Gestazione per altri” e interessi in conflitto (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
“Gestation for others” involves considerable doubts about its ethical and legal admissibility. The investigation is oriented, in particular, towards the distinction between “commercial” and “altruistic” surrogacy. Therefore, criticism is expressed about important sentences, which recognize in both of them a practice that “intolerably offends the dignity of women and deeply undermines human relations”. Finally, attention is paid to the problem of the status to be recognized for children born abroad through this practice and to the problem of risks associated with PMA, that is, those identifiable with the undesirable effects on the health of the mother and the unborn child.
Keywords: â€œCommercialâ€ surrogacy; â€œaltruisticâ€ surrogacy; conflict of interest; medically assisted procreation; health